Activation of coagulation and endothelium with concurrent impairment of anticoagulant mechanisms in patients with typhoid fever - De Jong, H; Parry, C; Van Der Vaart, T; Kager, L; Van Den Ende, S; Maude, R; Wijedoru, L; Ghose, A; Hassan, M; Hossain, M; Dondorp, A; Baker, S; et al. (Elsevier, 2018)
Objectives Typhoid fever caused by Salmonella Typhi remains a major burden worldwide. Gastrointestinal bleeding can be seen in up to 10 percent of patients and may be fatal. The coagulopathy, which may be the driver of this severe complication in patients with typhoid fever, however is ill defined. The aim of this study was to evaluate the activation of coagulation, anticoagulation, and fibrinolysis in patients with acute typhoid fever. Methods Parameters of coagulation and fibrinolysis were measured in 28 hospitalized patients with culture-confirmed or PCR-confirmed typhoid fever and compared to 38 age- and sex-matched healthy volunteers. Results Patients demonstrated activation of the coagulation system, as reflected by elevated in vitro thrombin generation and high plasma levels of fibrinogen, D-dimer and prothrombin fragment F1 + 2 in concert with consumption of coagulation factors resulting in a prolonged prothrombin-time and activated-partial-thromboplastin-time. Concurrently, the anticoagulant proteins, protein C and antithrom- bin, were significantly lower in comparison to healthy controls. Patients also demonstrated evidence of activation and inhibition of fibrinolysis and a marked activation of endothelial cells. The extent of coag- ulation activation was associated with the course of the disease, repeated testing during convalescence showed a return toward normal values. Conclusions Activation of coagulation is an important clinical feature of typhoid fever and is associated with severity of disease.